The Issues of Human Rights in the India-U.S. Relations - Zakharov Aleksey I. (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2016)
The article presents a brief overview of India-U.S. relations during the period of Narendra Modi’s government and Barack Obama’s administration. The author analyzes the dynamics of cooperation development after the victory of Bharatiya Janata Party in the 2014 Parliamentary elections in India and studies the key directions of bilateral agenda. The current condition of India-U.S. strategic dialogue and the influence of human rights issues on the countries’ cooperation are characterized.